Shooting Training Model Development Of Petanque For Beginners - Benny badaru; hasmyati hasmyati; Juhanis Juhanis; Nur Indah Atifah Anwar (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2021)
Petanque sports are games that prioritize very high shooting accuracy so that petanque sports are known as sports that have a high level of throwing accuracy. The purpose of this study was to develop a petanque sports shooting training model for beginners. This study uses a development research method from Borg and Gall. The research was conducted in the petanque field of South Sulawesi. The subjects in this study were South Sulawesi petanque athletes. Data analysis was performed using SPSS 21 software. Based on the data obtained, from the results of field trials and discussion of research results, it can be concluded that: through the validity test carried out using the expert justification test produced a product in the form of a Petanque shooting training model as many as 10 training models.